Patient‐reported outcome measures in pediatrics: An overview of reviews - Ruobing Lei; Jin Xiong; Haiyun Wang; Yuehuan Li; Janne Estill; Qiu Li; Yaolong Chen (Pediatric Discovery)
Abstract Patient‐reported outcome measures (PROMs) are standardized and validated self‐administered questionnaires for assessing patients' overall well‐being, disease burden, and health‐related quality of life. For children, their cognitive development, reading ability and language skills need to be considered when selecting the optimal PROM. High‐quality systematic reviews (SRs) can provide a comprehensive overview of the available PROMs and provide evidence‐based recommendations for pediatricians. Therefore, this study aims to provide an overview of pediatric SRs of PROMs. PubMed, Embase and Cochrane Library were searched to identify SRs of PROMs published in English focusing on the health of children and adolescents. Four researchers performed literature screening and data extraction, and evaluated the methodological quality of SRs using the A MeaSurement Tool to Assess systematic Reviews tool. Forty‐four SRs of PROMs published between 2006 and 2022 were included, recommending 123 PROMs, of which the most recommended were the pediatric quality of life inventory and its subscales and the EuroQol five dimension questionnaire. Thirty‐six conditions were addressed; the most frequent ICD‐11 category was “Mental, behavioral or neurodevelopmental disorders” (n = 9, 20.5%). The PROMs covered nine categories of contents to measure, the most frequent being the quality of life (n = 37, 30.1%). Content validity (n = 67, 54.5%) and internal consistency (n = 65, 52.9%) were the most commonly reported and measurement error (n = 10, 8.1%) was the least. The methodological and reporting of psychometric properties for SRs need further improvement. In addition, reporting of details such as the age when children should self‐report the measures needs also improvement.